Haji dan Kesehatan Masyarakat: Mengatasi Tantangan Pencegahan dan Pengelolaan Penyakit Menular - Kawasi, Akhmad; Sujatnika, Dadang Ahmad; Tabrani, Muahamad Doni (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2024)
This article discusses the significant public health challenges presented during the sacred ritual of Hajj for Muslims.. In this article, the risk of transmission of infectious diseases during Hajj is discussed due to the density of Jamaah, cultural diversity, and diverse sanitation conditions. Prevention efforts are also emphasized through vaccination, health screening, and education. In addition, mechanisms of detection, investigation, and response to outbreaks of infectious diseases are also discussed. This article highlights the challenges and opportunities in the prevention and management of infectious diseases during Hajj worship. In the face of the outbreak of infectious diseases during Hajj, it is important to have effective mechanisms in detecting, investigating, and responding to cases quickly and accurately. It involves coordination between health officials, Hajj authorities, and related agencies to conduct active surveillance of disease symptoms, conduct laboratory tests, and provide necessary medical treatment. Furthermore, education to the Hajj congregation about the symptoms of the disease and how to report suspicious health conditions is also an important part of the fight against the epidemic.During Hajj, there were a number of challenges to be faced in managing infectious diseases, ranging from high population densities to cultural differences among congregations. However, in the midst of these challenges, there is an opportunity to improve the effectiveness of public health efforts as a whole. With awareness of the risks of infectious diseases, medical and government teams can work together to create more effective and responsive prevention strategies. With good cooperation and proper education, the potential for spreading disease during Hajj can be significantly reduced, ensuring that this sacred worship journey takes place safely and healthy for all congregations